CONCEPTUAL PRINCIPLES OF SUSTAINABLE INCLUSIVE DEVELOPMENT OF SPORTS AND HEALTH SPHERE OF THE REGION (INNOVATIVE ECONOMY, 2021)
Tsymbaliuk S.M. CONCEPTUAL PRINCIPLES OF SUSTAINABLE INCLUSIVE DEVELOPMENT OF SPORTS AND HEALTH SPHERE OF THE REGIONPurpose. The aim of the article is scientific substantiation of the new concept of development of the sports and health sphere of the region, which is based on the observance of the principles of inclusive growth and achievement of the SDGs.Methodology of research. In the course of the research, the methods generally accepted in economics were used: monographic, system and structural, which were used in the development of the concept of sustainable inclusive development of the sports and health sphere of the region in the conditions of decentralization.Findings. It is determined that sustainable development and inclusive growth today are the newest models of social and economic growth, recognized by the world community. Taking into account this, and taking into account the processes of decentralization of management in Ukraine, the concept of sustainable inclusive development of the sports and health sphere of the region adapted to the new conditions is proposed. The goals of sustainable development are revealed, the achievement of which is influenced by the state and development of the sports and health sphere. The essence of inclusive growth is determined and the principles of inclusive development of the sports and health sphere of the region are singled out. Following the defined goals of sustainable development, the tasks of development of the sports and health sphere of the region are highlighted and the ways of their achievement are suggested. The basic conceptual idea of sustainable inclusive development of the sports and health sphere of the region is formed; the purposes, tasks, and ways of its realization are defined. The implementation of the proposed concept is outlined, and the impact of the development of sports and health in the region on improving the health, well-being, and quality of life of the community is substantiated.Originality. The concept of sustainable inclusive development of the sports and health sphere of the region is substantiated on the basis of its adaptation to the conditions of decentralization and introduction of the principles of inclusive growth and achievement of sustainable development goals to increase employment, spread a healthy lifestyle, expand opportunities to meet equal needs of the sport and health services.Practical value. The obtained results of the study are the basis for solving practical problems of sustainable inclusive development of sports and recreation in the regions of Ukraine under decentralization.Key words: sports and health sphere, the concept of development of sports and health sphere, sustainable development, inclusive growth, decentralization, the economic role of sports and health sphere.
Keywords: Key words; sports and health sphere; the concept of development of sports and health sphere; sustainable development; inclusive growth; decentralization; the economic role of sports and health sphere.